IMPLEMENTASI MODEL INKUIRI TERBIMBING DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR SUHU DAN PERUBAHANNYA - Nante, Oktavia Yolanda; Tandililing, Edy; Mursyid, Syukran (Universitas Tanjungpura, 2022)
AbstractThis study aims to improve the learning achievement of class VII students of SMP Negeri 20 Pontianak on temperature and changes by applying a guided inquiry model. This study used a pre-experimental design with a one-group pre-test and post-test design. Determination of the sample in this study using the Intact Group Random Sampling method with the number of class VII E SMP Negeri 20 Pontianak as many as 29 students. To see whether there is an influence in using the guided inquiry model on student learning outcomes at SMP Negeri 20 Pontianak, the classes selected to be sampled are VII E and VII F where class VII E is the control class and VII F is the experimental class. . The research instrument is a google form test to measure student achievement about temperature and change. Based on the data analyzed by Wilcoxon, there was an increase in student achievement from 33.7 to 77.5. The effectiveness of the application of